ETIOPATHOGENESIS, CLINICAL COURSE AND MANAGEMENT TACTICS OF ATONIC BLEEDING IN WOMEN AFTER CHILDBIRTH - Guljahon S. Babadjanova; Zarnigor F. Israilova (Central Asian Journal of Medicine, 2025)
Postpartum hemorrhage is considered a medical emergency and is one of the five leading causes of maternal death. Uterine atony and the risk factors leading to it are the main causes of bleeding after childbirth. In recent years, the rate of atonic bleeding has been increasing in many developed countries. Uterine atony is caused by an inadequate response of the smooth muscle fibers of the uterine body in response to endogenous oxytocin, which provides the contractile properties of the uterine muscle fibers. Normally, the contraction of the uterus after childbirth leads to compression of its spiral arteries, resulting in hemostasis, but as a result of changing in the muscle fibers of the spiral arteries and factors that prevent uterine contraction, uterine contraction does not occur or is insufficient after the third stage of labor, due to hypotonia, bleeding occurs from the spiral arteries, which leads to atonic type of bleeding after childbirth. This article briefly describes the factors that lead to atonic bleeding after childbirth, diagnostic criteria, management strategies and preventive measures.